1993
DOI: 10.1128/aac.37.11.2474
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-associated hemolysin and aggregation substance production contribute to virulence in experimental enterococcal endocarditis

Abstract: A rabbit endocarditis model was utilized to evaluate the virulence conferred by the conjugative plasmid pADi with the following strains: Enterococcus faecalis plasmid-free FA2-2 and FA2-2 containing plasmids pADi (hemolysin and aggregation substance positive), pAM9O58 (insertional inactivation of hemolysin), and pAM944 or pAM947 (insertional inactivation of aggregation substance). All isolates were similar in ability to produce endocarditis. Mean vegetation weight was greater in animals inoculated with strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
227
2
5

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(244 citation statements)
references
References 23 publications
10
227
2
5
Order By: Relevance
“…E. faecalis strains isolated from the faeces of healthy volunteers, liver transplant patients and blood cultures have been described and characterized for the presence of Esp and Agg elsewhere (Waar et al, 2002a). The enterococcal laboratory strains used in this study were: E. faecalis JH2-2 (Jacob & Hobbs, 1974), OG1X (Ike et al, 1983), OG1X(pAD1) (Clewell et al, 1982), OG1XE(pAD1) (Muscholl et al, 1993), OG1X(pAM373) (Clewell et al, 1985), FA2-2 (Clewell et al, 1982), FA2-2(pAD1) (Chow et al, 1993), MMH594 (Shankar et al, 1999), MMH594b (Shankar et al, 2001b), OG1RF (Dunny et al, 1978) and OG1RF(pCF10) (Dunny et al, 1981). All isolates were cultured from frozen stock on blood agar plates.…”
Section: Methodsmentioning
confidence: 99%
“…E. faecalis strains isolated from the faeces of healthy volunteers, liver transplant patients and blood cultures have been described and characterized for the presence of Esp and Agg elsewhere (Waar et al, 2002a). The enterococcal laboratory strains used in this study were: E. faecalis JH2-2 (Jacob & Hobbs, 1974), OG1X (Ike et al, 1983), OG1X(pAD1) (Clewell et al, 1982), OG1XE(pAD1) (Muscholl et al, 1993), OG1X(pAM373) (Clewell et al, 1985), FA2-2 (Clewell et al, 1982), FA2-2(pAD1) (Chow et al, 1993), MMH594 (Shankar et al, 1999), MMH594b (Shankar et al, 2001b), OG1RF (Dunny et al, 1978) and OG1RF(pCF10) (Dunny et al, 1981). All isolates were cultured from frozen stock on blood agar plates.…”
Section: Methodsmentioning
confidence: 99%
“…Some indirect evidence for this stems from the fact that for one and the same adhesin ASAl different results regarding binding to eukaryotic cells were observed. Chow et al (1993) (Berti et al, unpublished), using a rat endocarditis model, indicated that the presence or absence of the asal gene did not alter establishment of E. faecalis. The differences observed in those two studies could well be attributed to differences in the eukaryotic receptors ; however, other explanations cannot be excluded at the moment.…”
Section: Interaction With Bacterial and Eukaryotic Cellsmentioning
confidence: 99%
“…Cytolysin enhances the virulence of Enterococcus faecalis in animal models, such as murine peritonitis and rabbit endophthalmitis (Ike et al, 1984;Jett et al, 1992;Chow et al, 1993;Jett et al, 1994). Other factors include aggregation substance, which is a pheromone-inducible surface protein of E. faecalis and promotes mating aggregate formation during bacterial conjugation (Clewell, 1993).…”
Section: Introductionmentioning
confidence: 99%